The Zakat Distribution Management of Majlis Agama Islam Negeri Johor for the Mu’allaf Asnaf - Anuar, Puteh; Rashidi, Abbas; Abd Ghafar, Don; Zilal, Saari; Muhammad Syafiee, Elias (UKM, 2016)
This descriptive study aims to examine the management of zakat recipients mu’allaf in Johor Religious Council (JRC or MAINJ). The instruments used are document’s analysis and questionnaires. The sample consisted of 30 people among the new converts participated in this study and the study area is in the state of Johor. There are two constructs in this study: the perception of a new converts on the management of zakat distribution and the effects of the distribution of zakat to the new converts. The results discovered that the respondents are quite satisfied with the system of zakat distribution in JRC. Holistically, the study concluded that zakat distribution to new converts is very important to be implemented and managed properly for the welfare of the mu’allaf, especially in the affairs of the management of zakat distribution in JRC.